2017
DOI: 10.3945/ajcn.116.140392
|View full text |Cite
|
Sign up to set email alerts
|

Serum 25-hydroxyvitamin D and the risk of cardiovascular disease: dose-response meta-analysis of prospective studies

Abstract: During the past decade, an increasing number of prospective studies have focused on the association between vitamin D and cardiovascular disease (CVD). However, the evidence on the relation between serum 25-hydroxyvitamin D [25(OH)D] and the risk of overt CVD is inconclusive. We performed a dose-response meta-analysis to summarize and prospectively quantify the RR of low serum 25(OH)D concentration and total CVD (events and mortality). We identified relevant studies by searching PubMed and EMBASE up to Decembe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
96
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(116 citation statements)
references
References 78 publications
7
96
0
6
Order By: Relevance
“…According to the Institute of Medicine (IOM), vitamin D deficiency is defined as circulating 25-hy-droxyvitamin D (25[OH]D) level <50 nmol/L based on the optimal concentration for skeletal health (2). Interest has increased concerning the potential health consequences of vitamin D deficiency, such as increased risk of cardiovascular diseases, cancers, and Alzheimer's disease (3)(4)(5). Although observational data have demonstrated that poor vitamin D status is associated with increased risk of hypertension (6-9), randomized controlled trials (RCTs) have provided little support for the beneficial effect of vitamin D supplementation on blood pressure (10-13).…”
Section: Introductionmentioning
confidence: 99%
“…According to the Institute of Medicine (IOM), vitamin D deficiency is defined as circulating 25-hy-droxyvitamin D (25[OH]D) level <50 nmol/L based on the optimal concentration for skeletal health (2). Interest has increased concerning the potential health consequences of vitamin D deficiency, such as increased risk of cardiovascular diseases, cancers, and Alzheimer's disease (3)(4)(5). Although observational data have demonstrated that poor vitamin D status is associated with increased risk of hypertension (6-9), randomized controlled trials (RCTs) have provided little support for the beneficial effect of vitamin D supplementation on blood pressure (10-13).…”
Section: Introductionmentioning
confidence: 99%
“…In the study performed in northern Poland on 448 adults from February to mid-April, the mean 25(OH)D level was 14 ± 7 ng/mL years and 84% had a concentration of less than 20 ng/mL (< 50 nmol/L) [27]. Similar data came from a study on 274 elderly (mean age 69 years) postmenopausal women living in Warsaw [28] [30][31][32]. Zhang et al [33].…”
Section: Discussionmentioning
confidence: 55%
“…Compared to participants with adequate 25OHD concentrations (75 to 99.99 nmol/L), the adjusted hazard ratios (with 95% Cl) for CVD mortality in the 25OHD groups with 40 to 49.99, 30 to 39.99, and <30 nmol/L were 1.65 (1.1.39–1.97), 1.61 (1.46–1.77), and 2.21 (1.50–3.26), respectively. In line with these findings, a 2017 meta-analysis of 34 cohort studies with more than 180,000 participants [ 58 ] reported a progressive increase of total CVD events at circulating 25OHD levels < 50 nmol/L but no association of 25OHD with CVD events at levels between 50 and 137 nmol/L. With respect to CVD mortality, the risk increased constantly at circulating 25OHD levels < 100 nmol/L [ 58 ].…”
Section: Vitamin D Deficiency Bone Disorders and Cardiovascular mentioning
confidence: 78%
“…In line with these findings, a 2017 meta-analysis of 34 cohort studies with more than 180,000 participants [ 58 ] reported a progressive increase of total CVD events at circulating 25OHD levels < 50 nmol/L but no association of 25OHD with CVD events at levels between 50 and 137 nmol/L. With respect to CVD mortality, the risk increased constantly at circulating 25OHD levels < 100 nmol/L [ 58 ].…”
Section: Vitamin D Deficiency Bone Disorders and Cardiovascular mentioning
confidence: 78%